Pengaruh Trend Fashion dan Promosi Live Streaming TikTok Shop terhadap Keputusan Pembelian - Aretha, Nadia; Ramadhan, Brilliant Fitra; Yawan, Henri; Mashudan, Muhammad Vajri; Maesaroh, Syti Sarah (Universitas Pamulang, 2024)
This research examines how much influence fashion trends and TikTok Shop live streaming promotions have on consumer purchasing decisions, especially for students in Indonesia, when buying fashion products. Quantitative methods were used by distributing questionnaires on social media, and 51 respondents were obtained. The results of the analysis of the data received are that fashion trends partially do not have a significant influence, while the TikTok Shop live streaming promotion has a substantial effect on the dependent variable. Meanwhile, according to the results of the data, it was found that the two independent variables simultaneously had a significant influence. Looking at fashion trends in Indonesia that continue to grow as well as increasingly diverse forms of promotion, this research can be a consideration for manufacturers when planning their product marketing strategy.Penelitian ini mengkaji seberapa besar pengaruh trend fashion dan promosi live streaming TikTok Shop terhadap keputusan pembelian konsumen khususnya mahasiswa di Indonesia dalam membeli produk fashion. Digunakan metode kuantitatif dengan menyebarkan kuesioner di media sosial, dan diperoleh sebanyak 51 responden. Hasil analisis dari data yang diterima adalah trend fashion secara parsial tidak memiliki pengaruh yang cukup besar, sementara promosi live streaming TikTok Shop berpengaruh substansial terhadap variabel dependen. Adapun menurut hasil data, ditemukan bahwa kedua variabel independen secara simultan pun memiliki pengaruh yang signifikan. Melihat trend fashion di Indonesia yang terus berkembang, serta bentuk promosi yang semakin beragam, penelitian ini bisa menjadi suatu pertimbangan produsen ketika merencanakan strategi pemasaran produknya.